Mengatasi Dismenorea pada Remaja dengan Pola Makan Sehat - Novi Rida Eriyani; Lina Contesa (Jurnal Kabar Masyarakat, 2024)
Menstrual pain (dysmenorrhea) is a complaint experienced by 90% of women in the world, 10-15% of whom suffer from severe dysmenorrhea. One of the triggers for dysmenorrhea in adolescents is poor diet such as consuming junk food, smoking, and rarely exercising. These habits can worsen dysmenorrhea. This community service activity aims to increase the knowledge of adolescent girls about healthy eating patterns as a natural method to reduce dysmenorrhea. The target of the activity is adolescent girls in grade X of SMA Takwa Palembang. The activity was carried out by providing education to participants about what dysmenorrhea is, its causes, and how a healthy diet can help prevent or reduce menstrual pain. The results of the activity showed an increase in participants' knowledge about healthy eating patterns in dealing with menstrual pain as measured using a questionnaire. It is recommended that this program be followed by socialization to families and the provision of healthy food choices in school canteens to support the sustainability of the program's results.